Composite toughening material for oil well cement
By using composite toughening materials of powder polymer materials, elastic particles and whisker materials in oil well cement, the limitations and high cost of existing toughening materials are solved, the toughness and impact resistance of cement stone are significantly improved, the anti-aircraft ability is enhanced, and the construction performance is good, and it has a wide application prospect.
Patent Information
- Application Number
- CN202311179217.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
AI Technical Summary
Toughening materials in existing oil well cement have limitations and high costs, and it is difficult to effectively improve the comprehensive performance of cement rings, especially under stress changes, which are prone to brittle cracks, resulting in problems such as annular zone pressure.
A composite toughening material for oil well cement is used, including powder polymer material, elastic particles and whisker material. By adjusting the mass ratio and particle size of these materials, the cross network membrane structure and buffering effect are formed, and the toughness and impact resistance of cement stone are improved.
The composite toughening material significantly reduces the elastic modulus of cement stone in the range of 50-120℃, improves impact resistance, shortens the transition time of static gelation, and enhances anti-aircraft performance. It also does not affect the construction performance of thickening time, water loss and stability. It is low-cost and has wide application prospects.
Smart Images

Figure BDA0004446617370000071 
Figure BDA0004446617370000072 
Figure BDA0004446617370000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of drilling, and in particular to a composite toughening material for oil well cement. Background Art
[0002] With the increasing efforts in the development of unconventional energy such as shale gas, shale oil, and tight sandstone oil and gas in China, the pace of shale oil and gas development from non-mainstream to mainstream and from unconventional to "conventional" has been accelerated. The cement sheath in unconventional energy wells and gas storage wells is affected by stress changes during development and is prone to brittle fracture, which leads to failure of cement sheath integrity and causes problems such as annular pressure. To solve the above problems, cementing projects usually use tough cement slurry to ensure cementing quality, that is, adding toughening materials to cement to improve the toughness of cement stone and ensure the integrity of cement sheath. However, the current toughening materials have limitations and are relatively expensive, which increases the difficulty of subsequent promotion and use in oil field sites. Summary of the invention
[0003] The present application provides a composite toughening material for oil well cement, which can improve the comprehensive performance of cement paste.
[0004] This application adopts the following technical solutions:
[0005] The present application provides a composite toughening material for oil well cement, comprising a powder polymer material X and elastic particles Y, wherein the mass ratio of the powder polymer material X to the elastic particles Y is 1-1.5:1-1.5.
[0006] Furthermore, the composite toughening material for oil well cement also includes a whisker material Z, and the mass ratio of the powder polymer material X, the elastic particles Y, and the whisker material Z is 1-1.5:1-1.5:0.3-0.5.
[0007] Furthermore, the powder polymer material X includes vinyl acetate-ethylene copolymer and polyvinyl alcohol, and the mass ratio of the vinyl acetate-ethylene copolymer to the polyvinyl alcohol is 88:12.
[0008] Furthermore, the average particle size D50 of the powder polymer material X is 65 um.
[0009] Further, the elastic particles Y include hydrophilically modified polystyrene butadiene copolymer.
[0010] Furthermore, the particle size of the elastic particles Y is 100 meshes.
[0011] Further, the whisker material Z includes calcium carbonate whiskers.
[0012] Furthermore, the average particle size D50 of the whisker material Z is 6.8 um.
[0013] The present application also provides a cement slurry, comprising cement, the composite toughening material for oil well cement, a fluid loss reducer and water. The amount of the composite toughening material for oil well cement is 6% of the amount of cement, the amount of the fluid loss reducer is 2% of the amount of cement, and the amount of water is 44% of the amount of cement.
[0014] The present application also provides a cement slurry, comprising cement, the above-mentioned composite toughening material for oil well cement, silica fume, fluid loss agent, suspending agent, retarder and water. The amount of the composite toughening material for oil well cement is 6% of the amount of cement, the amount of silica fume is 35% of the amount of cement, the amount of the fluid loss agent is 2% of the amount of cement, the amount of the suspending agent is 1% of the amount of cement, the amount of the retarder is 2% of the amount of cement, and the amount of water is 55% of the amount of cement.
[0015] Compared with the prior art, this application has the following beneficial effects:
[0016] (1) In the temperature range of 50-120℃, the elastic modulus of toughened cement paste after adding composite toughening materials is significantly reduced, and the elastic modulus can be reduced by 26%-30% compared with the neat paste. Under the same addition amount, the composite toughening material has a better effect of reducing the elastic modulus than a single toughening raw material. Multiple toughening mechanisms work synergistically to achieve a positive mixing effect.
[0017] (2) After adding 6% of composite toughening material, the impact energy increased by 14.2%, thus improving the impact resistance of cement paste.
[0018] (3) After adding the composite toughening material, the static gelling transition time of the cement slurry is significantly shortened. When the amount is 6% added at 80°C, there is no gas leakage under the 200psi test pressure difference, which improves the anti-gas leakage performance of the cement slurry.
[0019] (4) The formed composite toughening material does not affect the construction performance such as thickening time, water loss and stability in the cement slurry system, and has good comprehensive performance.
[0020] (5) Compared with other composite toughening materials, the raw materials required for this composite toughening material are easy to obtain, the production is simple, the yield is high, the cost is low, and it has broad application prospects. DETAILED DESCRIPTION
[0021] The technical methods in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0022] The embodiment of the present application provides a composite toughening material for oil well cement, comprising a powder polymer material X and elastic particles Y, wherein the mass ratio of the powder polymer material X to the elastic particles Y is 1-1.5:1-1.5.
[0023] The powder polymer material X is vinyl acetate-ethylene copolymer and polyvinyl alcohol, and the mass ratio of vinyl acetate-ethylene copolymer to polyvinyl alcohol is 88:12. The average particle size D50 of the powder polymer material X is 65um. The powder polymer material X can form a cross-network membrane structure inside the cement stone, improve the toughness of the cement-based material through the good ductility of the organic material, and make the cement slurry have good anti-channeling performance.
[0024] Elastic particles Y are hydrophilic modified polystyrene butadiene copolymers, i.e. hydrophilic modified polystyrene butadiene copolymers. The particle size of elastic particles Y is 100 meshes. Elastic particles Y filled in cement paste can buffer the impact force and absorb part of the energy, improve the toughness, and contribute greatly to the impact resistance of cement paste. However, when added to a certain amount, it will affect the flexural strength.
[0025] The composite toughening material for oil well cement may further include a whisker material Z, and the mass ratio of the powder polymer material X, the elastic particles Y, and the whisker material Z is 1-1.5:1-1.5:0.3-0.5.
[0026] The whisker material Z is calcium carbonate whisker. The average particle size D50 of the whisker material Z is 6.8um. Fiber can play a role of "bridging" in the internal microstructure of cement paste to improve the toughness of cement paste. The general fiber material has a large aspect ratio and poor dispersion in cement paste. Whisker is a very small fiber material with mineral material characteristics, which avoids the disadvantage of poor dispersion of ordinary fiber and is easy to show a positive mixing effect after mixing with other elastic materials.
[0027] The composite toughening material for oil well cement may also include fillers, which are inert materials that do not participate in the reaction and play a role in uniform dispersion.
[0028] The composite toughening materials for oil well cement have the effect of reducing the elastic modulus of cement paste and have no adverse effects on the cement slurry thickening, water loss, stability and other properties.
[0029] The embodiments of the present application further provide a cement slurry, comprising cement, the composite toughening material for oil well cement, a fluid loss reducer and water.
[0030] The amount of composite toughening material used in oil well cement is 6% of the amount of cement.
[0031] The amount of fluid loss agent used is 2% of the amount of cement used. The fluid loss agent may be BCF-200S.
[0032] The amount of water used is 44% of the amount of cement used.
[0033] The embodiments of the present application further provide a cement slurry, comprising cement, the composite toughening material for oil well cement, silica fume, a fluid loss reducer, a suspending agent, a retarder and water.
[0034] The amount of composite toughening material used in oil well cement is 6% of the amount of cement.
[0035] The amount of silica fume used is 35% of the amount of cement used.
[0036] The amount of fluid loss agent used is 2% of the amount of cement used. The fluid loss agent may be BCF-200S.
[0037] The amount of the suspending agent is 1% of the amount of cement. The suspending agent may be BCJ-300S.
[0038] The amount of retarder used is 2% of the amount of cement used. The retarder may be BCR-320L.
[0039] The amount of water used is 55% of the amount of cement used.
[0040] The following is a detailed description with reference to specific embodiments:
[0041] Toughening Material Example 1
[0042] The powder polymer material X and the elastic particles Y are mixed in a ratio of 1:1 to obtain a composite toughening material for oil well cement.
[0043] Toughening Material Example 2
[0044] The powder polymer material X and the elastic particles Y are mixed in a ratio of 1:1.5 to obtain a composite toughening material for oil well cement.
[0045] Toughening Material Example 3
[0046] The powder polymer material X and the elastic particles Y are mixed in a ratio of 1.5:1 to obtain a composite toughening material for oil well cement.
[0047] Toughening Material Example 4
[0048] The powder polymer material X, elastic particles Y and whisker material Z are mixed in a ratio of 1:1:0.5 to obtain a composite toughening material for oil well cement.
[0049] Toughening Material Example 5
[0050] The powder polymer material X, elastic particles Y and whisker material Z are mixed in a ratio of 1:1.5:0.4 to obtain a composite toughening material for oil well cement.
[0051] Toughening Material Example 6
[0052] The powder polymer material X, elastic particles Y and whisker material Z are mixed in a ratio of 1.5:1:0.3 to obtain a composite toughening material for oil well cement.
[0053] Cement Slurry Example 1
[0054] Cement slurry formula: G grade cement + 6% toughening material + 2% fluid loss reducer BCF-200S + 44% water.
[0055] The composite toughening material for oil well cement in toughening material embodiment 1 is used to prepare cement slurry according to the above cement slurry formula.
[0056] Cement Slurry Example 2
[0057] Cement slurry formula: G grade cement + 6% toughening material + 2% fluid loss reducer BCF-200S + 44% water.
[0058] The composite toughening material for oil well cement in toughening material embodiment 2 is used to prepare cement slurry according to the above cement slurry formula.
[0059] Cement Slurry Example 3
[0060] Cement slurry formula: G grade cement + 6% toughening material + 2% fluid loss reducer BCF-200S + 44% water.
[0061] The composite toughening material for oil well cement in toughening material embodiment 3 is used to prepare cement slurry according to the above cement slurry formula.
[0062] Cement Slurry Example 4
[0063] Cement slurry formula: G grade cement + 6% toughening material + 2% fluid loss reducer BCF-200S + 44% water.
[0064] The composite toughening material for oil well cement in toughening material embodiment 2 is used to prepare cement slurry according to the above cement slurry formula.
[0065] Cement Slurry Example 5
[0066] Cement slurry formula: G grade cement + 6% toughening material + 2% fluid loss reducer BCF-200S + 44% water.
[0067] The composite toughening material for oil well cement in toughening material embodiment 2 is used to prepare cement slurry according to the above cement slurry formula.
[0068] Cement Slurry Example 6
[0069] Cement slurry formula: G grade cement + 6% toughening material + 2% fluid loss reducer BCF-200S + 44% water.
[0070] The composite toughening material for oil well cement in toughening material embodiment 2 is used to prepare cement slurry according to the above cement slurry formula.
[0071] Cement slurry comparative example 1
[0072] The only difference from cement slurry embodiment 1 is that only powder polymer material X is used as toughening material.
[0073] Cement slurry comparative example 2
[0074] The only difference from cement slurry embodiment 1 is that only elastic particles Y are used as toughening material.
[0075] Cement slurry comparative example 3
[0076] The only difference from cement slurry embodiment 1 is that only whisker material Z is used as toughening material.
[0077] Cement slurry comparative example 4
[0078] The only difference from cement slurry embodiment 1 is that the ratio of powder polymer material X to elastic particles Y is: X:Y=2:1.
[0079] Cement slurry comparative example 5
[0080] The only difference from cement slurry embodiment 1 is that the ratio of powder polymer material X to elastic particles Y is: X:Y=1:2.
[0081] Cement slurry comparative example 6
[0082] The only difference from cement slurry embodiment 2 is that the ratio of powder polymer material X, elastic particles Y and whisker material Z is: X:Y:Z=1:1:0.2.
[0083] Cement slurry comparative example 7
[0084] The only difference from cement slurry embodiment 2 is that the ratio of powder polymer material X, elastic particles Y and whisker material Z is: X:Y:Z=1:1:0.8.
[0085] Cement slurry comparative example 8
[0086] The only difference from cement slurry embodiment 2 is that the ratio of powder polymer material X, elastic particles Y and whisker material Z is: X:Y:Z=1:1:1.
[0087] Experimental Example 1
[0088] (1) At an experimental temperature of 80°C, a blank cement slurry sample without toughening material and cement slurry comparative samples 1, 2, and 3 prepared in correspondence with each other were evaluated. The results are shown in the following table:
[0089]
[0090] According to the experiment, the powder polymer material X, elastic particles Y and whisker material Z can improve the toughness of cement paste and have no adverse effects on the construction properties of cement paste such as water loss and thickening time.
[0091] (2) Cement slurry implementation sample 1, cement slurry comparative sample 4, and cement slurry comparative sample 5 prepared one by one in cement slurry embodiment 1, cement slurry comparative sample 4, and cement slurry comparative sample 5 were evaluated, with the elastic modulus being the key evaluation basis. The results are shown in the following table:
[0092]
[0093] Except for cement paste comparison sample 5, the elastic modulus performance of other samples is not inferior to that of a single toughening material with the same addition amount. Considering the elastic modulus and compressive strength, cement paste implementation sample 1 has a better overall performance. In summary, the composite toughening material of the present application improves the toughness of cement paste while having good impact resistance and anti-gas channeling effects.
[0094] (3) Cement slurry implementation sample 2, cement slurry comparison sample 6, cement slurry comparison sample 7, and cement slurry comparison sample 8 prepared in correspondence with cement slurry embodiment 4, cement slurry comparison example 6, cement slurry comparison example 7, and cement slurry comparison sample 8 were evaluated. The results are shown in the following table:
[0095]
[0096] According to the experiment, the elastic modulus of cement paste corresponding to cement paste sample 4 is the lowest, and the strength reduction is not obvious, showing a positive mixing effect. It is determined that the addition of whisker material Z produces a synergistic effect, which further reduces the elastic modulus of cement paste.
[0097] In summary, it can be seen that the toughening effect of the composite toughening material for oil well cement in toughening material embodiment 4 is the best.
[0098] Experimental Example 2
[0099] (1) According to the formulation in the following table, the cement slurry with the composite toughening material for oil well cement added in toughening material Example 4 was cured at 50°C, 80°C, 100°C and 120°C for 7 days, respectively, and compared with the neat slurry without the composite toughening material. The density of the cement slurry was 1.9 g / cm3. The experimental results are shown in the following table.
[0100]
[0101]
[0102]
[0103] In summary, within the range of 50-120°C, the elastic modulus of tough cement paste after adding composite toughening materials is significantly reduced, and the elastic modulus can be reduced by 26%-30% compared with the neat paste; within the range of 50-120°C, the strength of tough cement paste after adding composite toughening materials decreases to a certain extent, but still meets the technical requirements of conventional density tough cement paste 7d strength ≥28MPa in the "Technical Specifications for Tough Cementing".
[0104] (2) The composite toughening material of Example 4 of the toughening material with different amounts was added to the cement slurry and then cured at 80°C to conduct the impact resistance test of the cement paste. Cement slurry formula: G-grade cement + composite toughening material + 2% fluid loss agent BCF-200S + 44% water. The results are shown in the table below.
[0105] Composite toughening material content / %BWOC <![CDATA[Impact toughness / (kJ·m -2 )]]> 0 1.69 3 1.87 6 1.93 9 1.95
[0106] The impact energy of cement paste with the addition of composite toughening materials is significantly improved, and the toughness of cement paste is improved. When the addition amount of composite toughening materials is 6.0%, the impact energy increases by 14.2%, while when the addition amount is increased further, the improvement is limited.
[0107] (3) According to the industry standard "Evaluation Method for Oil Well Cement Admixtures Part 5: Anti-gas Channeling Agent SYT5504.5-2010", the anti-gas channeling performance of the composite toughening material of toughening material Example 4 was evaluated using a 7200 cement slurry channeling analyzer and a static gel strength analyzer. The results are shown in the table below.
[0108]
[0109] The cement slurry with composite toughening material added at 50℃ can withstand a test pressure difference of 150psi; at 80℃, it can withstand a test pressure difference of 200psi; at the same time, compared with the neat slurry, the addition of composite toughening material can shorten the static gelling transition time of tough cement slurry, and adding 6% composite toughening material can shorten the static gelling transition time by more than half. In summary, the composite toughening material has a certain anti-channeling effect and can improve the anti-channeling ability of cement slurry.
[0110] The above shows and describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present application. Without departing from the spirit and scope of the present application, the present application may have various changes and improvements, and the scope of protection required by the present application is defined by the attached claims, description and their equivalents.
[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A composite toughening material for oil well cement, characterized in that: It comprises a powder polymer material X and elastic particles Y, wherein the mass ratio of the powder polymer material X to the elastic particles Y is 1-1.5:1-1.
5.
2. The composite toughening material for oil well cement according to claim 1, characterized in that: It also includes a whisker material Z, and the mass ratio of the powder polymer material X, the elastic particles Y, and the whisker material Z is 1-1.5:1-1.5:0.3-0.
5.
3. The composite toughening material for oil well cement according to claim 1, characterized in that: The powder polymer material X includes vinyl acetate-ethylene copolymer and polyvinyl alcohol, and the mass ratio of the vinyl acetate-ethylene copolymer to the polyvinyl alcohol is 88:
12.
4. The composite toughening material for oil well cement according to claim 1, characterized in that: The average particle size D50 of the powder polymer material X is 65 um.
5. The composite toughening material for oil well cement according to claim 1, characterized in that: The elastic particles Y include hydrophilically modified polystyrene butadiene copolymer.
6. The composite toughening material for oil well cement according to claim 1, characterized in that: The particle size of the elastic particles Y is 100 meshes.
7. The composite toughening material for oil well cement according to claim 2, characterized in that: The whisker material Z includes calcium carbonate whiskers.
8. The composite toughening material for oil well cement according to claim 2, characterized in that: The average particle size D50 of the whisker material Z is 6.8 um.
9. A cement slurry, characterized in that: The invention comprises cement, the composite toughening material for oil well cement according to any one of claims 1 to 8, a fluid loss reducer and water; the amount of the composite toughening material for oil well cement is 6% of the amount of the cement, the amount of the fluid loss reducer is 2% of the amount of the cement, and the amount of water is 44% of the amount of the cement.
10. A cement slurry, characterized in that: The invention comprises cement, the composite toughening material for oil well cement according to any one of claims 1 to 8, silica fume, a fluid loss agent, a suspending agent, a retarder and water; the amount of the composite toughening material for oil well cement is 6% of the amount of the cement, the amount of the silica fume is 35% of the amount of the cement, the amount of the fluid loss agent is 2% of the amount of the cement, the amount of the suspending agent is 1% of the amount of the cement, the amount of the retarder is 2% of the amount of the cement, and the amount of water is 55% of the amount of the cement.